Religion and society among the Coorgs of South India - Srinivas, M. N. (New Delhi: Oxford University Press, 2003)
This is the late M.N. Srinivas' classic work on the religion and religious practices among the Coorgs in South India based on intensive field work. The author investigates the relationship between religion and society with particular reference to the people living in an isolated part of South Indi
Appendix 243-250p; Glossary 251-254p; Index 255-279p
Keywords: India; Religion; Sociology